Degradation of tannic acid by cold-adapted klebsiella sp NACASA1 and phytotoxicity assessment of tannic acid and its degradation products - Jadhav, Umesh; Kadu, Sudhir; Thokal, Nilesh; Padul, Manohar; Dawkar, Vishal V.; Chougale, Ashok D.; Salve, Abhay; Patil, Manoj (Environmental Science and Pollution Research, 2011)
The focus of the present study is to know the potential of bacterial isolate for tannic acid degradation at low temperature. Also, we tried to evaluate the suitability of phytotoxicity testing protocol for the determination of tannic acid toxicity. Screening for tannic acid degrading bacterial strains was carried out by using microbial isolation techniques. The 16S rDNA amplicon of the isolate was used to identify the isolate. The effect of different concentrations of tannic acid and its degradation products on germination of Vigna unguiculata was evaluated. The study was carried out to determine total sugar and starch content of the used seeds and even to check the presence of alpha-amylase activity during seed germination. The isolated bacterium was identified as Klebsiella sp NACASA1 and it showed degradation of tannic acid in 40 (+/- 0.85***) h at 15A degrees C and pH 7.0. A gradual decrease in root/shoot length was observed with increasing concentration of tannic acid. There was 95.11 (+/- 0.24**)% inhibition in alpha-amylase activity at 20,000 ppm tannic acid, as compared to control. No such effects were observed on germination, root-shoot length, and alpha-amylase activity with tannic acid degradation products. The results obtained confirmed that tannic acid may act as a toxic agent in plant cells. The simple biodegradation process presented in this study was found to be effective in reducing toxicity of tannic acid. Also, it reveals the potential of soil bacterium to degrade tannic acid at low temperature.
Keywords: Cold-adapted bacterium; Phytotoxicity; Tannic acid degradation